If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5x + -6 + 9 = 19 Reorder the terms: -6 + 9 + -5x = 19 Combine like terms: -6 + 9 = 3 3 + -5x = 19 Solving 3 + -5x = 19 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -5x = 19 + -3 Combine like terms: 3 + -3 = 0 0 + -5x = 19 + -3 -5x = 19 + -3 Combine like terms: 19 + -3 = 16 -5x = 16 Divide each side by '-5'. x = -3.2 Simplifying x = -3.2
| 0=8/12y-40 | | 7x-2=(x+1) | | -2x-8+6=7-4x-x | | -1(h+13)=5 | | 49-5=2a-3 | | 2(x-2)=-5 | | 2+4+3x=18 | | 14-(2c+5)=-7c+29 | | 5(2x-3)-x+8=13 | | 33=528x | | 10x+10 = +9x+15 | | X+4=-2-5x | | -2(x-4)=22 | | 7+4(7+4-25)= | | 4h+1+12h=36 | | 3x+57=7x+9 | | -(8y+1)-(-7y-3)=2 | | 15-29=2(x-3) | | 7+s^2(t+4-5r)= | | 5a+8+(-2)=-7 | | -(8y+1)-(-7y-3)=3 | | -(6y+4)-(-5y-6)=5 | | 100(z+3)-3(z-1)=4(z-3)+(z-1) | | y=2(-3) | | 11x=9x+6 | | 3x+10=8x-7 | | b=2f+8 | | 3(-3y+8)=-(-9y+120) | | 4m+18+4m=-20-42-2m | | 35(x+6)=35x-10 | | 1=5x+2 | | 17x+2y=3 |